Survey of Student’s Physical Education Learning Motivation at SD Negeri 09 Rawamangun during the Pandemic - Garasati, Fanny Givllia; Lanos, Muhsana El Cintami; Rizhardi, Rury (Perkumpulan Program Studi Doktor Pendidikan (PPSDP), 2024)
This study aimed to investigate the motivation levels of students at SDN 09 Rawamangun in the context of physical education during the pandemic. The primary focus was to assess how motivation influenced their engagement with physical education classes delivered remotely. Employing a survey research method, the study utilized a questionnaire as the main instrument for data collection. The sample comprised 70 students from SDN 09 Rawamangun, selected through total sampling, who participated in sports learning activities from home due to pandemic restrictions. The data analysis involved calculating the average response for each statement to gauge the motivation levels. The findings indicated that motivation in physical education was influenced by two main dimensions: intrinsic and extrinsic motivation. For the intrinsic dimension, 53 students (76%) were categorized as having very high motivation, while 17 students (24%) fell into the high motivation category. Conversely, in terms of extrinsic motivation, 32 students (46%) were rated in the very high category, and 38 students (54%) were categorized as having high motivation. These results suggest a strong overall motivation among students, with both intrinsic and extrinsic factors playing significant roles in their engagement with remote physical education.